Efforts to Prevent Marine Plastic Waste Based on Local Regulations and Participation of Coastal Communities in Semarang City - Novia Mungawanah (Rechtsvinding, 2026)
Marine plastic waste pollution is an increasingly urgent environmental problem in Semarang City, characterized by the increasing accumulation of plastic in coastal areas and marine waters which has an impact on ecosystem degradation, decline in the quality of fishery resources, and socio-economic vulnerability of fishing communities. This condition is triggered by high industrial and coastal economic activity, population density, and weak source-based waste management and low involvement of coastal communities. The urgency of preventing marine plastic waste requires a legal approach that not only focuses on regulations, but also on strengthening community participation as the main actor in coastal areas. This study aims to analyze the adequacy of local regulations in Semarang City in preventing marine plastic waste and formulate a prevention model based on regulations and participation of coastal communities. The research method used is normative juridical with legislative, conceptual, and policy approaches. Legal materials include laws and regulations in the field of waste management and the environment as well as relevant scientific literature. The results of the study show that regional regulations in Semarang City have not been specifically and integrated to regulate the prevention of marine plastic waste, and have not optimally accommodated the strategic role of coastal communities. This study concludes that the prevention of marine plastic waste needs to be directed at the harmonization of regional regulations, strengthening local institutions, and increasing the participation of coastal communities through community-based education, incentives, and supervision to realize sustainable and environmentally fair management of marine plastic waste.